Prevalence of glucose-6-phosphate dehydrogenase deficiency (G6PDd) and clinical implication for safe use of primaquine in malaria-endemic areas of Hainan Province, China - Zeng, Wen; Liu, Ning; Li, Yuchun; Gao, Ai; Yuan, Mengyi; Ma, Rui; Jiang, Na; Sun, Dingwei; Wang, Guangze; Feng, Xinyu (Frontiers in Public Health, 2022)
Abstract: Primaquine, the only licensed antimalarial drug for eradication of P. vivax and P. ovale malaria, may cause acute hemolytic anemia in individuals with glucose-6-phosphate dehydrogenase deficiency (G6PDd) during treatment. The different prevalence and distribution patterns of G6PDd in Hainan, the ancient malaria-endemic area, are unclear. This study included 5, 622 suspected malaria patients between 2009 and 2011 in 11 counties of Hainan. The G6PDd prevalence for different ethnic groups, genders, and counties were calculated and compared using χ2 test. Spatial cluster and Spearman rank correlation of G6PDd prevalence and malaria incidence were analyzed. The overall G6PDd prevalence of study population was 7.45%. The G6PDd prevalence of males, Li ethnic minority, and malaria patients was significantly higher than that of females, Han ethnic majority, and non-malarial patients (p < 0.01), respectively. The spatial cluster of G6PDd and malaria located in south-western and central-southern Hainan, respectively, with no significant correlation. The study provides essential information on G6PDd prevalence in ancient malaria-endemic areas of Hainan Province. We also highlight the need for a better understanding of the mechanisms underlying the relationship between G6PDd prevalence and malaria incidence. These findings provide a reference for the safety of the primaquine-based intervention, even after malaria elimination.